The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/ctr.14057
|View full text |Cite
|
Sign up to set email alerts
|

A single‐center long‐term experience with marginal donor utilization for heart transplantation

Abstract: Background: To evaluate the early and late outcome of heart transplantation (HT) using marginal (MDs) and optimal donors (ODs). Methods: Clinical records of recipients transplanted between July 2004 and December 2014 were retrospectively reviewed. MDs were defined as follows: age >55 years, high-dose inotropic support, left ventricular ejection fraction <45%, left ventricular hypertrophy, donor to recipient predicted heart mass ratio <0.86, ischemic time >4 hours. Results: A total of 412 (55%) recipients recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…2 In an attempt to resolve this problem, it is urged not only to promote organ donation but also to review the common regulation for donor organ selection criteria. [3][4][5] In the context of the deregulation of donor organ selection criteria, one of the global initiatives is to extend the existing donor pool by using so-called "marginal donor hearts," that is, organs that do not meet the entire range of criteria for optimal donor conditions. As a global consensus for alleviating donor heart criteria, the following donor selection factors were proposed: age, sex, or physique mismatch; drug abuse; hepatitis C; concomitant coronary artery disease; and impaired left ventricular (LV) function.…”
Section: Introductionmentioning
confidence: 99%
“…2 In an attempt to resolve this problem, it is urged not only to promote organ donation but also to review the common regulation for donor organ selection criteria. [3][4][5] In the context of the deregulation of donor organ selection criteria, one of the global initiatives is to extend the existing donor pool by using so-called "marginal donor hearts," that is, organs that do not meet the entire range of criteria for optimal donor conditions. As a global consensus for alleviating donor heart criteria, the following donor selection factors were proposed: age, sex, or physique mismatch; drug abuse; hepatitis C; concomitant coronary artery disease; and impaired left ventricular (LV) function.…”
Section: Introductionmentioning
confidence: 99%
“…Though we found that the use of a marginal donor was independently associated with post‐OHT mortality, prior studies have demonstrated relatively favorable outcomes with these donors 10,11 . Donor age in particular has been a focus of study.…”
Section: Resultsmentioning
confidence: 76%
“…Donor hearts and lungs were determined to be ECD organs if they satisfied two ECD criteria ( Table 1 ). ECD criteria were adapted from the literature describing extended criteria in hearts [ 1 , 3 , 4 , 5 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and lungs [ 2 , 6 , 7 , 8 , 17 ].…”
Section: Methodsmentioning
confidence: 99%